Towards Augmented Reality Support for Swarm Monitoring: Evaluating Visual Cues to Prevent Fragmentation - Henard, Aymeric; Peillard, Etienne; Riviere, Jeremy; Kubicki, Sebastien; Coppin, Gilles (IEEE transactions on visualization and computer graphics, 2025)
Swarm fragmentation, the breakdown of communication and coordination among robots, can critically compromise a swarm's mission. Integrating Augmented Reality support into swarm monitoring-especially through co-located visualisations anchored directly on the robots- may enable human operators to detect early signs of fragmentation and intervene effectively. In this work, we propose three localised visual cues-targeting robot connectivity, dominant decision influences, and movement direction-to make explicit the underlying Perception-Decision-Action (PDA) loop of each robot. Through an immersive Virtual Reality user study, 51 participants were tasked with both anticipating potential fragmentation and selecting the appropriate control to prevent it, while observing swarms exhibiting expansion, densification, flocking, and swarming behaviours. Our results reveal that a visualisation emphasising inter-robot connectivity significantly improves anticipation of fragmentation, though none of the cues consistently enhance control selection over a baseline condition. These findings underscore the potential of co-located AR-enhanced visual feedback to support human-swarm interaction and inform the design of future AR-based supervisory systems for robot swarms. A free copy of this paper and all supplemental materials are available at https://osf.io/49gny.